Examining the Impact of Audit Quality and Financial Performance on Corporate Tax Avoidance: Empirical Evidence from Public Listed Companies in Malaysia - Alaa Akram Sulaiman; Norfadzilah Rashid; Nadiah Abd Hamid (Indonesian Journal of Sustainability Accounting and Management, 2023)
The global financial crises, including the one experienced in Malaysia, have raised concerns about the reliability of accounting reports prepared by Malaysian listed companies. In response, regulatory and professional institutions have advocated for reforms aimed at promoting transparency in accounting reports. To this end, this study provides empirical evidence on the direct impact of audit quality and financial performance on corporate tax avoidance among companies listed on Bursa Malaysia. The panel data approach was used to collect data from 276 listed companies on Bursa Malaysia, with 1,656 observations covering a six-year period from 2013 to 2018. Multiple regression analysis was used to examine the relationship between audit quality, financial performance, and tax avoidance. The findings of this study indicate that audit quality and financial performance have a significant negative association with tax avoidance among Malaysian listed companies. These results suggest that firms with high audit quality and strong financial performance are less likely to engage in tax avoidance practices. The study has implications for policymakers and regulators, as it highlights the need for continued efforts to improve audit quality and financial reporting practices. Additionally, the findings suggest that measures aimed at improving financial performance among Malaysian listed companies may help reduce the prevalence of tax avoidance practices. Therefore, this study contributes to the ongoing debate on the effectiveness of regulatory and professional reforms aimed at promoting transparency and accountability in the financial reporting practices of Malaysian listed companies.